2023
DOI: 10.5114/aoms/156477
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning survival model for colorectal cancer patients (DeepCRC) with Asian clinical data compared with different theories

Abstract: IntroductionColorectal cancer (CRC) is the third most common cancer. Precise prediction of CRC patients’ overall survival (OS) probability could offer advice on its treatment. Neural network (NN) is the first-class algorithm, but a consensus on which NN survival models are better has not been established yet. A predictive model on CRC using Asian data is also lacking.Material and methodsWe conducted 8 NN survival models of CRC (n = 416) with different theories and compared them using Asian data.ResultsDeepSurv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…DeepSurv converges deep neural network and CPH regression, and it can find out about the complex and nonlinear relationships between prognostic clinical variables and an individual's probability of mortality in true world, which has shown huge potential on medical field (24)(25)(26). Our previous studies have also demonstrated DeepSurv may outperform CPH in predicting tumor patients' survival (27,28). Therefore, we construct survival models using both CPH and DeepSurv algorithm this time, using all variables collected or LASSO to filter potential predictive clinical features, and chose the better one to serve as the final model.…”
Section: Discussionmentioning
confidence: 99%
“…DeepSurv converges deep neural network and CPH regression, and it can find out about the complex and nonlinear relationships between prognostic clinical variables and an individual's probability of mortality in true world, which has shown huge potential on medical field (24)(25)(26). Our previous studies have also demonstrated DeepSurv may outperform CPH in predicting tumor patients' survival (27,28). Therefore, we construct survival models using both CPH and DeepSurv algorithm this time, using all variables collected or LASSO to filter potential predictive clinical features, and chose the better one to serve as the final model.…”
Section: Discussionmentioning
confidence: 99%
“…Katzman et al [ 12 ] proposed the DeepSurv method to solve this problem, which has been applied in some tumor prognosis studies, such as lung cancer and head and neck cancer[ 12 , 29 , 30 ]. Our previous study also demonstrated that it is better than traditional algorithms such as CPH[ 31 ]. Therefore, we built a deep-learning-based model based on the DeepSurv algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common cancer and the second leading cause of cancer death worldwide. About 1 in 10 cancer patients aged < 50 years old is diagnosed with CRC [ 1 , 2 ]. The 5-year survival rate is < 15%, which causes a heavy burden on human health [ 3 ].…”
Section: Introductionmentioning
confidence: 99%